A Note on Unrestricted Composition. (September 2015) - McCarthy, Timothy
<x xml:space="preserve">Abstract</x> I discuss a general limitative consequence of the unrestricted mereological composition thesis. The unrestricted composition thesis, which is roughly the assertion that every plurality of objects possesses a fusion or sum, is shown to be in conflict with general existence‐conditions for certain categories of mereologically non‐composite objects. The conclusion is that the unrestricted composition thesis, which is a maximizing principle about what aggregates exist, places sharp limits on what unaggregated items can exist.